Nitro-Substituted aromatic thiolate self-assembled monolayers: structural properties and electron transfer upon resonant excitation of the tail group - Waske, Prashant Ankushrao; Wächter, Tobias; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2014)
Self-assembled monolayers (SAMs) of HS-(C6H4)n-NO2 (nPT-NO2), abbreviated individually as PT-NO2, BPT-NO2, and TPT-NO2 for n = 1, 2, and 3, respectively, were prepared on Au(111) substrates and characterized by X-ray photoelectron spectroscopy, near-edge X-ray absorption ﬁne structure spectroscopy, and resonant Auger electron spectroscopy. All molecules in the ﬁlms were found to be bound to the substrate via the thiolate anchor and to have an upright orientation. The introduction of the nitro tail group had a positive eﬀect on the quality of the PT-NO2 SAMs, which was superior to that of the nonsubstituted analogues. The parameters of the BPT-NO2 and TPT-NO2 ﬁlms were similar to those of the analogous nonsubstituted systems. The [N 1s]π* and [O 1s]π* decay spectra of all studied nPT-NO2 SAMs did not exhibit any trace of charge (electron) transfer (CT) through the molecular framework to the substrate, following the resonant excitation of the tail group. This was explained by the energy considerations hindering CT to the substrate but enabling a reverse process (ICT), viz., the neutralization of the core ionized state by electron transfer from the substrate/molecular backbone. Traces of this process could be tentatively identiﬁed as an admixture of resonant contributions to the nonresonant decay spectra at the O K-edge. The experimental data suggest that only the ring adjacent to the nitro group was involved in the ICT process.
Gesehen am 11.08.2020